Thin layer preparation process of NiMC self-growing hydrogen evolution cathode

By using a thin layer preparation process of NiMC self-grown hydrogen evolution cathode on the porous nickel substrate, the high cost of cathode catalyst in water electrolysis hydrogen production and the repetition and uniformity in large-area electrode preparation are solved, and an efficient and stable hydrogen evolution reaction is achieved.

CN119615241APending Publication Date: 2025-03-14DALIAN UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411964088.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the cathode catalyst for hydrogen production by electrolysis of water is high, especially the use of platinum-based precious metal catalysts has led to an increase in production costs, and there are problems of repeatability and uniformity in batch preparation of large-area electrodes.

Method used

A thin layer preparation process of NiMC (M=Cu, Mo, Co, Fe, Mn) self-grown hydrogen-excitation cathode was adopted. By uniformly mixing the metal salt with the reducing agent solution, thin layer electrodes were formed on the porous nickel substrate by ultrasonic spraying, screen printing, brush coating or dipping, and NiMC structure was formed by heat treatment.

Benefits of technology

It realizes uniform growth of NiMC self-growth structure on porous nickel substrate, without the need for precious metal addition, reduces the cost of electrode preparation, improves hydrogen evolution activity and stability, and is suitable for batch preparation of large-area HER electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615241A_ABST
    Figure CN119615241A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of water electrolysis hydrogen production, and particularly relates to a thin layer preparation process of a NiMC self-growing hydrogen evolution cathode, and M is Cu, Mo, Co, Fe and Mn. According to the invention, the thin chromatography hydrogen cathode is formed by self-growth on the surface of a porous nickel-based material subjected to earlier-stage pretreatment. The self-growth process is realized through processes of automatic spraying, screen printing, brush coating, dipping and the like, and in-situ growth of the hydrogen evolution active component NiMC on the porous nickel substrate can be realized. The method has the advantages that under the condition of high-temperature heating, the NiMC self-supporting structure is formed through in-situ growth in the instantaneous process of automatically spraying on the surface of the porous nickel-based material, and the formed hydrogen evolution cathode is free of noble metal load; the precision and the repeatability are relatively high; the catalyst has high HER activity and stability in an alkaline medium; the preparation process is simple, quality control is easy to realize, the process repeatability is good, and the prepared electrode has relatively high repeatability and uniformity and is suitable for batch preparation of large-area HER electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogen production by water electrolysis, and in particular relates to a thin layer preparation process of a NiMC (M=Cu, Mo, Co, Fe, Mn) self-grown hydrogen evolution cathode. Background Art

[0002] Hydrogen energy is considered to be an indispensable part of the future national energy architecture, and is mainly divided into gray hydrogen, blue hydrogen, and green hydrogen. Green hydrogen does not produce any greenhouse gas emissions during the production process, which helps to alleviate global climate change; when converted into electricity and heat energy, only water is produced, and no other harmful gases are produced; it is widely used in transportation (such as fuel cell vehicles, hydrogen trains) and industrial production (such as steel smelting, chemical raw materials). At the same time, the production of green hydrogen is based on renewable resources, so it has a sustainable supply capacity, which is different from the limited and destructive exploitation of traditional fossil energy. At present, water electrolysis to produce hydrogen is one of the most promising technologies for the industrial production of green hydrogen. It has many advantages such as simple system structure, clean and environmentally friendly production process, high purity of hydrogen production, modular design and high product purity.

[0003] AEM water electrolysis hydrogen production technology combines the advantages of alkaline water electrolysis and PEM water electrolysis, uses non-precious metal catalysts, and reduces material costs. During the operation, no concentrated alkali solution is required, which reduces the use of corrosive chemicals and further reduces the complexity and operating costs of the system. The key components of the AEM electrolytic cell mainly include the oxygen evolution anode, the anion exchange membrane, and the hydrogen evolution cathode. These components are assembled together into a membrane electrode. The use of low-concentration alkali solution as a hydrogen evolution medium can significantly improve the membrane electrode performance of AEM. In the hydrogen evolution reaction, platinum-based precious metal catalysts dominate with their excellent performance. However, in order to promote the large-scale commercial application of anion exchange membrane (AEM) water electrolysis technology, reducing production costs has become an urgent problem to be solved. Therefore, the development of cathode catalysts with low platinum content or even platinum-free, such as single-atom catalysts, platinum alloy catalysts, and non-platinum catalysts, has become the focus of current research.

[0004] In alkaline media, transition metals such as copper, cobalt, nickel, and molybdenum exhibit high hydrogen evolution activity due to their incomplete filling characteristics of d orbitals. Among them, NiMo alloy materials have become one of the most promising hydrogen evolution electrodes due to their unique performance advantages. Qian et al. (Qian G, Chen J, Jiang W, et al. Strong electronic coupling of CoNi and N-doped-carbon for efficient urea-assisted H2 production at a large current density [J]. Carbon Energy, 2023, 5 (12): e368.) found that introducing Mo elements into Ni-based or Co-based catalysts can significantly improve their HER performance. Damian et al. (Damian A, Gmanovic S. Ni and Ni-Mo Hydrogen Evolution Electrocatalysts Electrodeposited in a Polyaniline Matrix [J]. Journal of Power Sources, 2006, 158 (1): 464-476.) first reported the superiority of NiMo materials in HER catalysis. They used the alloying of Ni and Mo to electro-deposit on the surface of the conductive polymer polyaniline (PANI) to obtain a rough NiMo alloy structure, which can regulate the electron density in the d-shell after nickel-molybdenum alloying, thereby improving the HER kinetics. Han et al. (Han L, Dong S, Wang E, et al. Transition-Metal (Co, Ni, and Fe)-Based Electrocatalysts for the Water Oxidation Reaction [J]. Advanced Materials, 2016, 28 (42): 9266-9291.) found that the doping on the transition metal surface can not only change the local electronic structure of the catalyst, resulting in a narrowing of the d-band gap, thereby improving the conductivity, but also regulate the adsorption energy of the metal active band during the reaction, thereby enhancing the HER activity. For example, doping the C element on the surface of NiMo alloy changes the electronic configuration of the transition metal d orbital, thereby enhancing the conductivity of the catalyst. This change enables the catalyst surface to more effectively adsorb hydrogen ions, reducing the hydrogen adsorption energy, thereby promoting the HER process; in addition, the non-metallic elements doped on the transition metal surface can also form more heterogeneous surface structures. These heterogeneous surface structures provide additional active sites for the catalyst, further enhancing the HER activity.

[0005] At present, the electrode methods for preparing self-grown Ni-based bimetallic alloy structures include hydrothermal method, electrodeposition method, electrospinning method, etc. Ning et al. (Ning M, Zhang F, Wu L, et al. Boosting efficient alkaline freshwater and seawater electrolysis via electrochemical reconstruction [J]. Energy & Environmental Science, 2022, 15 (9): 3945-3957.) synthesized Fe-doped Ni & Ni0.2Mo0.8N (Fe0.01-Ni & Ni0.2Mo0.8N) compounds on the surface of nickel foam by hydrothermal method. After rapid electrochemical reconstruction, the Fe-doped Ni & Ni0.2Mo0.8N compounds were reconstructed into Fe and Mo co-doped NiO (Fe0.01 & Mo-NiO). At 10 mA cm -2 and 500mA·cm -2At , the minimum HER overpotentials are 26 and 135 mV, respectively. Wei et al. (Wei C, Sun Y, et al. Surface Composition Dependent Ligand Effect in Tuning the Activity of Nickel-Copper Bimetallic Electrocatalysts toward Hydrogen Evolution in Alkaline [J]. Journal of the American Chemical Society, 2020, 142, 7765-7775.) prepared a self-grown electrode of NiCu bimetallic alloy structure by electrodeposition. By combining theoretical calculations and experimental measurements, it was proved that the various active sites formed by the combination of NiCu are close to the optimal hydrogen adsorption energy. It broadens the applicability of d-band theory in the prediction of metal electrocatalyst activity and improves the deep understanding of the alkaline HER mechanism. Sun et al. (Sun M, Ye Q, Lin L, et al. NiMo solid-solution alloy porous nanofiber as outstanding hydrogen evolution electrocatalyst [J]. J Colloid Interface Sci, 2023, 637: 262-270.) designed and synthesized a highly active HER electrocatalyst NiMo solid solution alloy porous nanofiber by electrospinning, oxidation and high-temperature reduction. The alloying of Ni and Mo regulates the electronic structure of the active sites to promote water adsorption, water dissociation and optimized desorption of H2. Therefore, the optimized NiMo porous nanofibers have high HER activity in 1M KOH electrolyte, providing 100, 500 and 1000 mA cm at overpotentials of 69, 208 and 300 mV. -2 , and 100mA·cm -2 High durability over 60 hours.

[0006] Hu Han et al. (CN118756204A) disclosed a method for preparing a small-area self-supporting hydrogen evolution electrode by a hydrothermal method. A small piece of nickel felt is added to a reactor, and then a nickel salt solution and a molybdenum salt solution are added to carry out a double decomposition reaction. The generated catalyst precursor is in situ grown on the nickel felt to obtain a self-grown electrode semi-finished product. The self-grown electrode semi-finished product is cleaned and dried and placed in a tubular furnace for thermal reduction to obtain the Ni / NiMo@MoO self-supporting electrode. The hydrogen evolution cathode is heated in 1M KOH at 100 mA cm -2The hydrogen evolution overpotential is about 266mV. The electrode size produced by this method is not suitable for industrial production. Zhang Hongliang et al. (CN117926306A) disclosed a highly efficient amorphous Ni or NiM (M = Mo, Fe, Co) hydrogen evolution electrode and its preparation method. Amorphous Ni or NiM particles are sputtered on a pretreated substrate by magnetron sputtering. The amorphous Ni or NiM particles have a larger electrochemical active area, which increases the reaction sites and hydrogen evolution activity; at the same time, the spontaneous oxidation of amorphous Ni or NiM particles generates a stable Ni / NiO heterostructure or NiM / NiMO heterostructure, which enhances the hydrogen evolution activity. However, the use of carbon paper as the electrode substrate material is not suitable for the assembly of industrial battery stacks. Huang Jianfeng et al. (CN118957655A) disclosed a method for preparing a highly efficient hydrogen evolution catalyst Mo / Mo-2C. The method comprises mixing and stirring molybdenum powder and carbon powder and reacting them at high temperature under an argon atmosphere to obtain a black powder Mo / Mo-2C catalyst having good hydrogen evolution activity. However, the powder obtained by this method needs to be supported on the surface of a base material and a binder needs to be added.

[0007] At present, the research on NiMo hydrogen evolution electrocatalysts has made significant progress. Many NiMo-based materials have shown excellent performance comparable to platinum-based precious metals. However, there are few patent reports on the preparation process for large-scale preparation to ensure electrode repeatability and uniformity. In the existing preparation process, the hydrothermal synthesis process can easily prepare self-grown electrodes with excellent hydrogen evolution activity, but the size of the synthesized thin-layer self-grown electrode material is limited by the reaction equipment, and it is difficult to achieve batch preparation of large-area electrodes, which to a certain extent hinders its widespread application; although the electrodeposition method can grow two-dimensional materials on a conductive substrate, in the process of large-area electrode deposition, the complex current distribution of the electrochemical system makes it difficult to achieve uniform growth of two-dimensional materials; the electrospinning method easily optimizes the electronic structure by adjusting the composition of the precursor solution, and then obtains nanofiber materials through multi-step thermal reduction. Although this method has certain flexibility in material synthesis, the ultra-high voltage environment and slow injection time required in the electrospinning synthesis process limit the widespread application of this method. Summary of the invention

[0008] In view of the problems existing in the above-mentioned self-grown hydrogen evolution cathode material preparation technology with Ni as the main metal, the present invention proposes a thin layer preparation process of NiMC (M = Cu, Mo, Co, Fe, Mn) self-grown hydrogen evolution cathode. First, the metal salt is mixed and dissolved in deionized water, and stirred evenly with the reducing agent solution to obtain a self-growing solution; or the metal salt and the reducing agent are dissolved in deionized water respectively. Then, a thin layer preparation process (including ultrasonic spraying, screen printing, brushing, immersion, etc.), heat treatment and other processes are used to obtain a thin layer electrode material. By preparing a thin layer hydrogen evolution cathode material through a self-growing cathode process, the uniform growth of the hydrogen evolution active component NiMC on a porous nickel substrate can be achieved. Its characteristic advantages are: (1) In the instantaneous process of preparing a thin layer electrode, a NiMC self-growing structure is formed by in-situ growth on the porous nickel-based surface, and the hydrogen evolution cathode grown on the surface does not have precious metals added, which effectively reduces the preparation cost of the electrode. (2) The self-growing solution has good stability and dispersibility, and can be evenly dispersed and grown on a porous nickel substrate. (3) The prepared NiMC electrode has high HER activity and stability in alkaline medium. (4) The self-grown hydrogen evolution cathode preparation process is simple, easy to achieve quality control, and has good process repeatability, which is suitable for the batch preparation of large-area HER electrodes (hydrogen evolution electrodes).

[0009] The technical solution of the present invention is as follows:

[0010] A thin layer preparation process of a NiMC self-grown hydrogen evolution cathode, the specific steps are:

[0011] Step 1. Pretreatment of porous nickel electrode substrate: Use porous nickel-based material as electrode substrate, wash it with acetone, anhydrous ethanol and deionized water respectively, etch it in water-soluble acid, and finally dry it for use.

[0012] Step 2. Preparation of metal salt and reducing agent solution: dissolve nickel salt and second component M metal salt in deionized water, mix and stir with reducing agent to obtain self-growth solution A; or dissolve nickel salt and second component M metal salt in deionized water to obtain metal salt mixed solution B, and dissolve or dilute the reducing agent alone with deionized water to obtain reducing agent solution D; wherein the second component M is Cu, Mo, Co, Fe or Mn.

[0013] Step 3. Thin layer preparation process:

[0014] (1) Automatic spraying method: Install a temperature-controllable vacuum adsorption pump on the surface of the automatic spraying heating platform; place the porous nickel electrode substrate obtained in step 1 on the heating platform and fix it; turn on the vacuum adsorption pump and automatically spray the self-growth solution A prepared in step 2 onto the surface of the porous nickel-based material; after the surface of the material is dried, spray the self-growth solution A repeatedly; after spraying, let it dry naturally at room temperature.

[0015] (2) Screen printing method: The porous nickel electrode substrate obtained in step 1 is placed on a heating platform and fixed; a layer of the metal salt mixed solution B prepared in step 2 is applied on the surface of the porous nickel electrode substrate by screen printing technology, and then a layer of reducing agent solution D is applied on the surface, and the above operation is repeated; after the application is completed, it is allowed to dry naturally at room temperature.

[0016] (3) Immersion method: Place the porous nickel electrode substrate obtained in step 1 in a vacuum operating box, and immerse the porous nickel electrode substrate multiple times in the self-growth solution A prepared in step 2. Repeat the immersion operation after no liquid flows on the surface of the porous nickel electrode substrate. After the immersion is completed, allow it to dry naturally at room temperature.

[0017] (4) Brushing method: The porous nickel electrode substrate obtained in step 1 is fixed on a heating table, and the self-growth solution A prepared in step 2 is manually brushed on the surface of the porous nickel-based material; after the surface of the substrate is dried, the self-growth solution A is repeatedly brushed; after the brushing is completed, it is allowed to dry at room temperature.

[0018] By adopting any of the above methods, an electrode with a thin layer is prepared.

[0019] Step 4. Heat treatment: The thin-layer electrode prepared in step 3 is subjected to heat treatment to form a NiMC structure on the surface of the electrode material, and finally a NiMC self-grown hydrogen evolution cathode is obtained.

[0020] Furthermore, in step 1, the porous nickel-based material is nickel foam or nickel felt.

[0021] Furthermore, in step 1, the water-soluble acid is one or a mixture of two or more of hydrochloric acid, oxalic acid, and phosphoric acid.

[0022] Furthermore, in step 1, the mass concentration of the water-soluble acid used for etching is 5-20wt.%, the etching method is a water bath, and the water bath temperature is 75°C-100°C.

[0023] Furthermore, in step 2, the mass concentration of nickel salt in the self-growing solution A and the metal salt mixed solution B is 10 to 50 g·L -1 The mass concentration of the second component metal salt is 5 to 50 g·L -1 .

[0024] Furthermore, in step 2, the reducing agent is one or a mixture of two or more of borohydride, hydrazine hydrate, ethylene glycol, and glycerol, wherein the mass concentration of the reducing agent solution C is 1 to 30 g·L -1 .

[0025] Furthermore, in step 3, in the automatic spraying method, screen printing method and brush coating method, the heating temperature of the heating table is between room temperature and 200°C; in the immersion method, the controllable air pressure of the vacuum operating box is between normal pressure and 100 Pa, and the temperature can be set between normal temperature and 80°C; in the screen printing method, the mesh size of the screen is between 50 and 400.

[0026] Furthermore, in step 3, the self-growing solution A carries 0.1 to 4 mL cm per unit area on the surface of the porous nickel electrode substrate. -2 The total amount of metal salt solution B and reducing agent solution D loaded per unit area on the surface of the porous nickel electrode substrate is 0.1-4 mL cm -2 The total volume of the metal salt solution B is 1:1, and the volume ratio of the metal salt solution B and the reducing agent solution D is 1:1.

[0027] Furthermore, in step 4, heat treatment is performed in a tubular furnace under a nitrogen, air or mixed hydrogen atmosphere, the heat treatment temperature is 200° C. to 500° C., and the time is 1 to 3 hours.

[0028] The present invention has the following beneficial effects:

[0029] (1) This method adopts a thin-layer electrode preparation process, which has the advantages of simple process, easy quality control, good process repeatability, etc., and is suitable for batch preparation of large-area HER electrodes; the prepared hydrogen evolution cathode has high repeatability and uniformity, and its performance is comparable to that of commercial Pt / C electrodes, with a short production cycle, high production efficiency and stable electrode quality, which can meet the requirements of industrial production. (2) The NiMC self-supporting structure is formed by in-situ growth on the porous nickel-based surface, which effectively improves the problems of small specific surface area, poor electron transport performance, low exposure of active sites and slow reaction kinetics of porous nickel-based materials, is more conducive to the release of hydrogen products, and further enhances conductivity; there is no precious metal loading. (3) The thin-layer cathode prepared by this method is greatly improved by etching process, constructing bimetallic alloy and non-metallic element doped structure, and using heat treatment process to greatly improve the hydrogen evolution catalytic performance. The obtained hydrogen evolution cathode has extremely high hydrogen evolution activity and stability. At 1 mol·L -1 The cathode material for hydrogen evolution was used in a KOH electrolyte solution at a current density of 10 mA cm -2 The hydrogen evolution overpotential generated under these conditions is similar to that of commercial carbon-supported platinum. -2 The hydrogen evolution overpotential is less than 400mV when the temperature is 500mA·cm -2 At a current density of 1.38 volts, the maximum performance decay rate is only 0.212 mV·h -1; The relative error of the performance of samples at different positions on the large-area electrode is less than 5%. (4) The self-supporting electrode prepared by this method is assembled on the membrane electrode cathode to test the electrochemical performance. NiFeMo is used as the oxygen evolution anode. The current density at 2V can reach 800-1200mA·cm -2 ; at 500mA·cm -2 Under the same conditions, a constant current stability test was carried out and the voltage was still below 2V after running for 1000h. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a schematic flow diagram of a thin layer preparation process of a NiMC self-grown hydrogen evolution cathode.

[0031] Figure 2 is a scanning electron microscope image of the electrode prepared in Example 1 of the present invention.

[0032] Figure 3 This is the electrochemical hydrogen evolution cathode polarization curve of the effect of the second component metal type on the HER activity of the hydrogen evolution cathode in Example 2 of the present invention.

[0033] Figure 4 This is the electrochemical hydrogen evolution cathode polarization curve showing the effect of the porous nickel-based material type used in Example 3 of the present invention on the HER activity of the hydrogen evolution cathode.

[0034] Figure 5 This is an electrochemical hydrogen evolution cathode polarization curve showing the effects of the acid concentration and etching temperature used for etching on the HER activity of the hydrogen evolution cathode in Example 4 of the present invention.

[0035] Figure 6 This is the electrochemical hydrogen evolution cathode polarization curve of the effect of nickel salt concentration on the HER activity of the hydrogen evolution cathode in Example 5 of the present invention.

[0036] Figure 7 This is the electrochemical hydrogen evolution cathode polarization curve of the effect of molybdenum salt concentration on the HER activity of the hydrogen evolution cathode in Example 6 of the present invention.

[0037] Figure 8 This is the electrochemical hydrogen evolution cathode polarization curve showing the effect of the reducing agent concentration used in Example 7 of the present invention on the HER activity of the hydrogen evolution cathode.

[0038] Fig. 9 This is the electrochemical hydrogen evolution cathode polarization curve showing the effect of the reducing agent solvent used in Example 8 of the present invention on the HER activity of the hydrogen evolution cathode.

[0039] Fig.10 This is the electrochemical hydrogen evolution cathode polarization curve showing the effect of the spraying amount per unit electrode area on the HER activity of the hydrogen evolution cathode in Example 9 of the present invention.

[0040] Fig.11 This is the electrochemical hydrogen evolution cathode polarization curve showing the effect of the heating temperature on the HER activity of the hydrogen evolution cathode in Example 10 of the present invention.

[0041] Fig.12 This is the electrochemical hydrogen evolution cathode polarization curve of the effect of the heat treatment temperature on the HER activity of the hydrogen evolution cathode in Example 11 of the present invention.

[0042] Fig.13 This is the electrochemical hydrogen evolution cathode polarization curve of the effect of heat treatment time on the HER activity of the hydrogen evolution cathode in Example 12 of the present invention.

[0043] Fig.14 This is the HER stability test curve of the electrode prepared in Example 13 of the present invention in a H cell as a hydrogen evolution cathode.

[0044] Fig.15 This is a performance curve of the effect of the membrane electrode operating temperature on the water electrolysis activity in Example 14 of the present invention.

[0045] Fig.16 This is the water electrolysis stability curve of the membrane electrode prepared in Example 15 of the present invention. DETAILED DESCRIPTION

[0046] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0047] The process of preparing a thin layer of a NiMC self-grown hydrogen evolution cathode of the present invention is as follows: Figure 1 As shown, the specific embodiments are as follows:

[0048] Example 1: SEM Scanning Electron Microscope Test of Hydrogen Evolution Cathode

[0049] (1) Substrate pretreatment: A nickel felt with a thickness of 0.3 mm was used as the substrate and cut into 6 cm × 1 cm strip electrodes. The electrodes were ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times in sequence, and then etched in 20 wt.% phosphoric acid at 100 °C for 10 min. The electrodes were dried at room temperature and set aside for use.

[0050] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 10 g·L -1 The mass concentration of the second component metal salt is 20 g·L -1 ; Then add the same volume of 100% propylene glycol solution.

[0051] (3) Preparation of thin-layer electrodes by automatic spraying: The substrate material is fixed on the heating platform of the automatic spraying, and the temperature of the heating platform is set to 80°C. After the temperature stabilizes, the self-growing solution is sprayed evenly on the surface of the porous nickel substrate by automatic spraying. After the surface of the substrate is dried, the self-growing solution is sprayed repeatedly. After spraying is completed, it is dried at the spraying temperature.

[0052] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 200°C, and the heating time is 1 hour. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0053] (5) SEM results are as follows Figure 2 As shown, it can be seen that the surface cracks of the prepared hydrogen evolution self-growth electrode are larger and the gaps are deeper, exposing more active sites, which can improve the HER activity of the hydrogen evolution cathode.

[0054] Example 2: Effect of the second component M on the HER activity of the hydrogen evolution cathode

[0055] Prepare the self-supporting layer, the preparation process is as follows:

[0056] (1) Substrate pretreatment: A 0.3 mm thick nickel foam substrate was cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed three times with anhydrous ethanol and deionized water, then etched in 10 wt.% phosphoric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0057] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The second component is Mo, Cu, Co, Fe, and Mn, and its mass concentration is 20 g·L -1 ; To prepare NiMoC, NiCuC, NiCoC, NiFeC, NiMnC amorphous hydrogen evolution cathode. Sodium borohydride was dissolved in the same volume of deionized water with a concentration of 5 g·L -1 , added dropwise to the metal salt solution.

[0058] (3) Preparation of thin-layer electrodes by automatic spraying: The substrate material is fixed on the heating platform of the automatic spraying, and the temperature of the heating platform is set to 140°C. After the temperature stabilizes, the self-growing solution is sprayed evenly on the surface of the porous nickel substrate by automatic spraying. After the surface of the substrate is dried, the self-growing solution is sprayed repeatedly. After spraying is completed, it is dried at the spraying temperature.

[0059] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a mixed hydrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 350°C, and the heating time is 1 hour. After the heat treatment is completed, the target hydrogen evolution electrode is obtained.

[0060] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Figure 3 As shown. It can be seen that the addition of metal Mo as the second component can improve the HER activity of the hydrogen evolution cathode.

[0061] Example 3: Effect of substrate material on HER activity of hydrogen evolution cathode

[0062] (1) Substrate pretreatment: 0.3 mm thick nickel foam and nickel felt were used as substrates, cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times, then etched in 1 M HCl solution at 80 °C for 10 min, and finally dried at room temperature for use.

[0063] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 50 g·L -1 The mass concentration of the second component metal salt is 50 g·L -1 ; Then add the same volume of 20% glycerol solution diluted with deionized water.

[0064] (3) Preparation of thin-layer electrodes by automatic spraying: The substrate material is fixed on the heating platform of the automatic spraying, and the temperature of the heating platform is set to 180°C. After the temperature stabilizes, the self-growing solution is sprayed evenly on the surface of the porous nickel substrate by automatic spraying. After the substrate surface is dried, the self-growing solution is sprayed repeatedly. After spraying is completed, it is dried at the spraying temperature.

[0065] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a mixed hydrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 500°C, and the annealing time is 1 hour. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0066] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Figure 4 As shown. It can be seen that nickel foam as a substrate material can improve the HER activity of the hydrogen evolution cathode compared to nickel felt.

[0067] Example 4: Effect of Etching Acid Concentration and Etching Temperature on HER Activity of Hydrogen Evolution Cathode

[0068] (1) Substrate pretreatment: A nickel foam with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 1 cm strips, and ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times, and then etched in 5 wt.% oxalic acid at 80°C for 10 min, in 10 wt.% oxalic acid at 90°C for 10 min, and in 20 wt.% oxalic acid at 100°C for 10 min, respectively. Finally, it was dried at room temperature and set aside.

[0069] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 10 g·L -1 The mass concentration of the second component metal salt is 5 g·L -1 ; Then add the same volume of 60% glycerol solution diluted with deionized water.

[0070] (3) Preparation of thin-layer electrodes by automatic spraying: The substrate material is fixed on the heating platform of the automatic spraying, and the temperature of the heating platform is set to 200°C. After the temperature stabilizes, the self-growing solution is sprayed on the surface of the porous nickel substrate by automatic spraying. After the surface of the substrate is dried, the self-growing solution is sprayed repeatedly. After spraying is completed, it is dried at the spraying temperature.

[0071] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 200°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0072] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Figure 5 As shown. It can be seen that increasing the acid concentration used for etching and increasing the etching temperature can improve the HER activity of the hydrogen evolution cathode.

[0073] Example 5: Effect of nickel salt concentration on HER activity of hydrogen evolution cathode

[0074] (1) Substrate pretreatment: A nickel felt with a thickness of 0.3 mm was used as the substrate, cut into strips of 6 cm × 1 cm, and ultrasonically treated in acetone for 30 min. Then, it was rinsed three times with anhydrous ethanol and deionized water in sequence, and then etched in 10 wt.% dilute hydrochloric acid at 100 °C for 10 min. Finally, it was dried at room temperature and used for later use.

[0075] (2) Prepare a mixed solution of metal salts and a reducing agent solution: Dissolve the mixed metal salts in deionized water, where the mass concentration of nickel salt is 10 g·L -1 、30g·L -1 , 50g·L -1 The mass concentration of the second component metal salt is 20 g·L -1 ; Dissolve sodium borohydride in the same volume of deionized water to a concentration of 10 g·L -1 , used as reducing agent solution.

[0076] (3) Preparation of thin-layer electrodes by screen printing: The substrate material is fixed on a heating table, the temperature of the heating table is set to 100°C, and the mesh number of the screen is 50. After the temperature stabilizes, a layer of metal salt solution is applied on the porous nickel substrate by screen printing technology. Then, a layer of reducing agent solution is applied in the same way. After the surface of the substrate is dried, the metal salt mixed solution and the reducing agent solution are repeatedly applied alternately. After the application is completed, it is left to dry naturally at room temperature.

[0077] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 350°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0078] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Figure 6 As shown in the figure, with the increase of nickel salt concentration, the HER activity of hydrogen evolution cathode first increases and then decreases. -1 HER activity is highest when

[0079] Example 6: Effect of Molybdenum Salt Concentration on HER Activity of Hydrogen Evolution Cathode

[0080] (1) Substrate pretreatment: A nickel foam with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times in sequence, then etched in 10 wt.% dilute hydrochloric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0081] (2) Prepare a mixed solution of metal salts and a reducing agent solution: Dissolve the mixed metal salts in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 5 g·L -1 , 20g·L -1 , 50g·L -1 , dissolve sodium borohydride in the same volume of deionized water to a concentration of 20 g·L -1 , used as reducing agent solution.

[0082] (3) Preparation of thin-layer electrodes by screen printing: The substrate material is fixed on a heating table, the temperature of the heating table is set to 120°C, and the mesh number of the screen is 100. After the temperature stabilizes, a layer of metal salt mixed solution is applied on the porous nickel substrate by screen printing technology. Then, a layer of reducing agent solution is applied in the same way. After the substrate surface is dried, the metal salt solution and reducing agent solution are repeatedly applied alternately. After the application is completed, it is left to dry naturally at room temperature.

[0083] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 500°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0084] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Figure 7 As shown in Figure 2, it can be seen that with the increase of molybdenum salt concentration, the HER activity of hydrogen evolution cathode continues to increase. -1 HER activity is highest when

[0085] Example 7: Effect of reducing agent concentration on HER activity of hydrogen evolution cathode

[0086] (1) Substrate pretreatment: A 0.3 mm thick nickel foam substrate was cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed three times with anhydrous ethanol and deionized water, then etched in 20 wt.% oxalic acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0087] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 20 g·L -1, and then add the same volume of ethylene glycol solution diluted with deionized water to a concentration of 20%, 60%, and 100%.

[0088] (3) Preparation of thin-layer electrodes by immersion method: Place the substrate material in a vacuum operating box, set the ambient pressure to 100 Pa, set the temperature to 20°C, and wait for the temperature to stabilize. Immerse the porous nickel-based substrate material in the self-growth solution for multiple times. After no liquid flows on the substrate surface, repeatedly immerse it in the mixed solution of metal salt solution and reducing agent. After the immersion is completed, let it dry naturally at room temperature.

[0089] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in an air atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 500°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0090] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Figure 8 As shown. It can be seen that the increase of reducing agent concentration can improve the HER activity of hydrogen evolution cathode.

[0091] Example 8: Effect of reducing agent solvent on HER activity of hydrogen evolution cathode

[0092] (1) Substrate pretreatment: A nickel foam with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times in sequence, then etched in 10 wt.% dilute hydrochloric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0093] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 50 g·L -1 ; Ethylene glycol, hydrazine hydrate and glycerol were added as reducing agents in the same volume, and the concentration of each reducing agent after mixing was 50%.

[0094] (3) Preparation of thin-layer electrodes by immersion method: Place the substrate material in a vacuum operating box, set the ambient pressure to 50,000 Pa, set the temperature to 50°C, and wait for the temperature to stabilize. Immerse the porous nickel-based substrate material in the self-growth solution for multiple times. After no liquid flows on the substrate surface, repeatedly immerse it in the mixed solution of metal salt solution and reducing agent. After the immersion is completed, let it dry naturally at room temperature.

[0095] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in an air atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 350°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0096] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Fig. 9 As shown. It can be seen that hydrazine hydrate as a reducing agent solvent has a higher hydrogen evolution cathode HER activity.

[0097] Example 9: Effect of coating amount per unit area of ​​electrode on HER activity of hydrogen evolution cathode

[0098] (1) Substrate pretreatment: A 0.3 mm thick nickel foam substrate was cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed three times with anhydrous ethanol and deionized water, then etched in 10 wt.% phosphoric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0099] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 50 g·L -1 ; Then add the same volume concentration of 100% hydrazine hydrate solution.

[0100] (3) Preparation of thin-layer electrodes by immersion method: Place the substrate material in a vacuum operating box, set the ambient pressure to normal pressure, set the temperature to 80°C, and wait until the temperature stabilizes. Immerse the porous nickel-based substrate material in the self-growth solution multiple times. After no liquid flows on the surface of the substrate, repeatedly immerse it in a mixed solution of a metal salt solution and a reducing agent. After the immersion is completed, allow it to dry naturally at room temperature. Control the amount of solution so that the immersion amount per unit electrode area is 0.1 to 4 mL cm -2 .

[0101] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a mixed hydrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 500°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0102] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min-1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Fig.10 As shown. It can be seen that increasing the coating amount per unit area of ​​the electrode can improve the HER activity of the hydrogen evolution cathode.

[0103] Example 10: Effect of heating temperature on HER activity of hydrogen evolution cathode

[0104] (1) Substrate pretreatment: A 0.3 mm thick nickel foam substrate was cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed three times with anhydrous ethanol and deionized water, then etched in 10 wt.% phosphoric acid at 100 °C for 60 min, and finally dried at room temperature for use.

[0105] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 20 g·L -1 , and then add the same volume concentration of 20% hydrazine hydrate solution.

[0106] (3) Preparation of thin-layer electrodes by screen printing: The substrate material is fixed on a heating table, the temperature of the heating table is set to 160°C, and the mesh number of the screen is 400. After the temperature stabilizes, a layer of metal salt solution is applied on the porous nickel substrate by screen printing technology. Then, an organic phase reducing agent solution is quickly applied. After the substrate surface is dried, the metal salt solution and the reducing agent solution are repeatedly applied alternately. After the application is completed, it is left to dry naturally at room temperature.

[0107] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 350°C, and the annealing time is 3h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0108] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Fig.11 As shown, it can be seen that with the increase of heating temperature, the HER activity of the hydrogen evolution cathode first increases and then decreases, and the HER activity is the highest when the heating temperature is 140°C.

[0109] Example 11: Effect of heat treatment temperature on HER activity of hydrogen evolution cathode

[0110] (1) Substrate pretreatment: A nickel foam with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times in sequence, then etched in 10 wt.% dilute hydrochloric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0111] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 20 g·L -1 ; Then add the same volume of hydrazine hydrate solution diluted with deionized water to a concentration of 20%.

[0112] (3) Preparation of thin-layer electrodes by brush coating: Place the substrate material on a heating platform, turn on the bottom adsorption device, set the temperature of the heating platform to 80°C, and after the temperature stabilizes, manually apply the mixed self-growth solution on the surface of the porous nickel substrate. After the substrate surface is dried, repeat the brushing of the self-growth solution several times. After brushing, wait until it is dry at room temperature.

[0113] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The starting temperature of the heat treatment is 25°C, the heat treatment temperature is set to 200°C to 500°C, and the annealing time is 3h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0114] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Fig.12 As shown. It can be seen that the increase of heat treatment temperature can improve the HER activity of hydrogen evolution cathode.

[0115] Example 12: Effect of heat treatment time on HER activity of hydrogen evolution cathode

[0116] (1) Substrate pretreatment: A nickel foam with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 1 cm strips, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times in sequence, then etched in 10 wt.% dilute hydrochloric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0117] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 20 g·L -1; Then add the same volume of ethylene glycol solution diluted with deionized water to a concentration of 60%.

[0118] (3) Preparation of thin-layer electrodes by brush coating: Place the substrate material on a heating table, turn on the bottom adsorption device, set the temperature of the heating table to 100°C, and after the temperature stabilizes, manually brush the self-growing solution on the surface of the porous nickel substrate until it is evenly mixed. After the substrate surface is dried, repeat the brushing of the self-growing solution several times. After brushing, wait until it is dry at room temperature.

[0119] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in a nitrogen atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is set to 500°C, and the annealing time is 1 to 3 hours. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0120] (5) Performance test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 . Perform linear scan at a scan rate of 1mV / s. The test results are as follows Fig.13 As shown. It can be seen that increasing the heat treatment time can improve the HER activity of the hydrogen evolution cathode.

[0121] Example 13: HER stability test of hydrogen evolution cathode in H cell

[0122] (1) Substrate pretreatment: A nickel felt with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 8 cm sheets, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times, then etched in 10 wt.% phosphoric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0123] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 50 g·L -1 ; Then add the same volume of hydrazine hydrate solution diluted with deionized water to a concentration of 60%.

[0124] (3) Preparation of thin-layer electrodes by brush coating: Place the substrate material on a heating platform, turn on the bottom adsorption device, set the temperature of the heating platform to 120°C, and after the temperature stabilizes, manually apply the mixed self-growth solution on the surface of the porous nickel substrate. After the substrate surface is dried, repeat the brushing of the self-growth solution several times. After brushing, wait until it is dry at room temperature.

[0125] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in an air atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 500°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0126] (5) Stability test: The target hydrogen evolution electrode was placed in an H-type electrolytic cell, the electrolyte was 1M KOH, the reference electrode was a mercury oxide electrode, and the counter electrode was a platinum electrode; the test temperature was 25 °C, and the cathode was fed with N2 at a rate of 20 mL min -1 At 500mA·cm -2 The electrode stability was tested under constant current conditions for 500 hours. The test results are as follows: Fig.14 As shown. It can be seen that at 500mA·cm -2 Under the current density of , it has good stability in the 500-hour test.

[0127] Example 14: Effect of membrane electrode operating temperature on water electrolysis activity

[0128] (1) Substrate pretreatment: A nickel felt with a thickness of 0.3 mm was used as the substrate, cut into 6 cm × 8 cm sheets, ultrasonically treated in acetone for 30 min, then rinsed with anhydrous ethanol and deionized water three times, then etched in 10 wt.% phosphoric acid at 100 °C for 10 min, and finally dried at room temperature for use.

[0129] (2) Preparation of self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30 g·L -1 The mass concentration of the second component metal salt is 50 g·L -1 ; Then add the same volume of 60% glycerol solution diluted with deionized water.

[0130] (3) Preparation of thin-layer electrodes by brush coating: Place the substrate material on a heating platform, turn on the bottom adsorption device, set the temperature of the heating platform to 140°C, and after the temperature stabilizes, manually apply the mixed self-growth solution on the surface of the porous nickel substrate. After the substrate surface is dried, repeat the brushing of the self-growth solution several times. After brushing, wait until it is dry at room temperature.

[0131] (4) Post-preparation heat treatment: The substrate with the grown catalyst is transferred to a tube furnace and heat treated in an air atmosphere. The heat treatment starting temperature is 25°C, the heat treatment temperature is 500°C, and the annealing time is 2h. After the heat treatment, the target hydrogen evolution electrode is obtained.

[0132] (5) Preparation of anode electrode: Use NiFeMoB anode powder catalyst and brush it on the surface of specially treated nickel felt to form a microporous layer anode oxygen evolution electrode.

[0133] (6) Assembly of membrane electrode: First, place the hydrogen evolution cathode on the central flow field area of ​​the cathode plate, and then place a layer of sealing gasket. The sealing gasket is a PTFE gasket with a thickness of 0.3 μm, cut into a rectangular frame that does not cover the central flow field area to ensure that the catalyst layer can contact the alkaline membrane. Cover the alkaline membrane on the upper end of the cathode catalyst layer, and the anode microporous layer is also in contact with the alkaline membrane. Try to adjust the position so that the cathode and anode microporous layers overlap, and then place another layer of sealing gasket, and finally place the anode plate. After the membrane electrode assembly is stacked, tighten the screws to complete the assembly of the electrolyzer.

[0134] (7) Performance test: 1M KOH was selected as the feed material for both cathode and anode, and the anode feed rate was 2 mL min -1 , the cathode feed rate was 2.5 mL min -1 ; The test temperature is 20℃~80℃. The test performance adopts constant current test method, setting the step current 0~4A, the step is 200mA, the test time is 30s at each current value, and measuring the change of voltage at different given current values. The test results are as follows Fig.15 As shown. It can be seen that with the increase of working temperature, the activity of electrolyzed water will also increase.

[0135] Example 15: Electrolyzed water stability test

[0136] (1) Cathode preparation:

[0137] ① Substrate pretreatment: The substrate used for self-supporting catalyst loading is a porous nickel-based material, such as nickel foam, nickel felt, etc. The porous nickel-based material with a thickness of 0.3 mm is used as the substrate, cut into 20 mm × 20 mm blocks, ultrasonically cleaned in acetone for 30 minutes, and then rinsed three times with anhydrous ethanol and deionized water; the rinsed substrate is placed in a 10wt.% oxalic acid solution, etched in a 90℃ water bath for 10 minutes, taken out and cooled to room temperature, and then rinsed three times with anhydrous ethanol and deionized water, and finally dried at room temperature for use.

[0138] ②Prepare the self-growth solution: Dissolve the metal salt in deionized water, where the mass concentration of nickel salt is 30g·L -1 The mass concentration of the second component metal salt is 50 g·L -1 , then add the same volume of 100% ethylene glycol solution.

[0139] ③ Preparation of thin-layer electrodes by brush coating: Place the substrate material on a heating platform, turn on the bottom adsorption device, set the temperature of the heating platform to 160°C, and after the temperature stabilizes, manually apply the mixed self-growth solution on the surface of the porous nickel substrate. After the substrate surface is dried, repeat the brushing of the self-growth solution several times. After brushing, wait until it is dry at room temperature.

[0140] ④ Heat treatment: The prepared electrode material is placed in a tubular furnace in a mixed hydrogen atmosphere and heated at 500°C for 2 hours. After heat treatment, a NiMoC self-supporting layered hydrogen electrode is obtained.

[0141] (2) Preparation of anode electrode: NiFeMoB anode powder catalyst is brushed on the surface of specially treated nickel felt to form a microporous layer anode oxygen evolution electrode.

[0142] (3) Assembly of membrane electrode: First, place the hydrogen evolution cathode on the central flow field area of ​​the cathode plate, and then place a layer of sealing gasket. The sealing gasket is a PTFE gasket with a thickness of 0.3 μm, cut into a rectangular frame that does not cover the central flow field area to ensure that the catalyst layer can contact the alkaline membrane. Cover the alkaline membrane on the upper end of the cathode catalyst layer, and the anode microporous layer is also in contact with the alkaline membrane. Try to adjust the position so that the cathode and anode microporous layers overlap, and then place another layer of sealing gasket, and finally place the anode plate. After the membrane electrode assembly is stacked, tighten the screws to complete the assembly of the electrolyzer.

[0143] (4) Assembly of membrane electrode: First, place the hydrogen evolution cathode on the central flow field area of ​​the cathode plate, and then place a layer of sealing gasket. The sealing gasket is a PTFE gasket with a thickness of 0.3 μm, cut into a rectangular frame that does not cover the central flow field area to ensure that the catalyst layer can contact the alkaline membrane. Cover the alkaline membrane on the upper end of the cathode catalyst layer, and the anode microporous layer is also in contact with the alkaline membrane. Try to adjust the position so that the cathode and anode microporous layers overlap, and then place another layer of sealing gasket, and finally place the anode plate. After the membrane electrode assembly is stacked, tighten the screws to complete the assembly of the electrolyzer.

[0144] (5) Stability test: The anode feed was 1M KOH, and the feed rate was 2 mL min -1 , the cathode feed is H2, and the feed rate is 2.5 mL min -1 ; The test temperature is 80℃. The stability test adopts the chronoamperometry, setting the constant voltage value to 2V, and measuring the change of current over time. The test results are as follows Fig.16 As shown. It can be seen that in the stability test of 1000h at 2V voltage, the performance gradually decayed after 500h. It can be seen that the electrode can operate stably in the first 500h, and there will be a small decay after 500h, and the voltage decay rate is about 0.212mV / h.

Claims

1. A thin layer preparation process of NiMC self-grown hydrogen evolution cathode, characterized in that: The specific steps are: Step 1. Pretreatment of porous nickel electrode substrate: using porous nickel-based material as electrode substrate, washing with acetone, anhydrous ethanol and deionized water respectively, etching in water-soluble acid, and finally drying for standby use; Step 2. Preparation of metal salt and reducing agent solution: dissolving nickel salt and second component M metal salt in deionized water, and then mixing with reducing agent and stirring evenly to obtain self-growth solution A; or dissolving nickel salt and second component M metal salt in deionized water to obtain metal salt mixed solution B, and dissolving or diluting reducing agent alone with deionized water to obtain reducing agent solution D; wherein second component M is Cu, Mo, Co, Fe or Mn; Step 3. Thin layer preparation process: (1) Automatic spraying method: Install a temperature-controllable vacuum adsorption pump on the surface of the automatic spraying heating platform; place the porous nickel electrode substrate obtained in step 1 on the heating platform and fix it; turn on the vacuum adsorption pump and automatically spray the self-growth solution A prepared in step 2 onto the surface of the porous nickel-based material; after the surface of the material is dried, spray the self-growth solution A repeatedly; after spraying is completed, let it dry naturally at room temperature; (2) Screen printing method: The porous nickel electrode substrate obtained in step 1 is placed on a heating platform and fixed; a layer of the metal salt mixed solution B prepared in step 2 is applied on the surface of the porous nickel electrode substrate by screen printing technology, and then a layer of reducing agent solution D is applied on the surface, and the above operation is repeated; after the application is completed, it is allowed to dry naturally at room temperature; (3) Immersion method: The porous nickel electrode substrate obtained in step 1 is placed in a vacuum operating box, and the porous nickel electrode substrate is immersed in the self-growth solution A prepared in step 2 for multiple times. After no liquid flows on the surface of the porous nickel electrode substrate, the immersion operation is repeated; after the immersion is completed, it is allowed to dry naturally at room temperature; (4) Brush coating method: The porous nickel electrode substrate obtained in step 1 is fixed on a heating platform, and the self-growth solution A prepared in step 2 is manually brushed on the surface of the porous nickel-based material; after the surface of the substrate is dried, the self-growth solution A is repeatedly brushed; after the brush coating is completed, it is allowed to dry at room temperature; Using any of the above methods, an electrode with a thin layer is prepared; Step 4. Heat treatment: The thin-layer electrode prepared in step 3 is subjected to heat treatment to form a NiMC structure on the surface of the electrode material, and finally a NiMC self-grown hydrogen evolution cathode is obtained.

2. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In the step 1, the porous nickel-based material is nickel foam or nickel felt.

3. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In step 1, the water-soluble acid is one or a mixture of two or more of hydrochloric acid, oxalic acid and phosphoric acid.

4. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In the step 1, the mass concentration of the water-soluble acid used for etching is 5-20wt.%, and the method used is a water bath with a water bath temperature of 75°C-100°C.

5. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In step 2, the mass concentration of nickel salt in the growth solution A and the metal salt mixed solution B is 10-50 g·L -1 The mass concentration of the second component metal salt is 5 to 50 g·L -1 .

6. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In step 2, the reducing agent is one or a mixture of two or more of borohydride, hydrazine hydrate, ethylene glycol, and glycerol, wherein the mass concentration of the reducing agent solution C is 1 to 30 g·L -1 .

7. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In step 3, in the automatic spraying method, screen printing method and brush coating method, the heating temperature of the heating table is between room temperature and 200°C; in the immersion method, the controllable air pressure of the vacuum operating box is between normal pressure and 100 Pa, and the temperature can be set between normal temperature and 80°C; in the screen printing method, the mesh number of the screen is between 50 and 400.

8. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: In step 3, the self-growing solution A carries 0.1 to 4 mL cm per unit area on the surface of the porous nickel electrode substrate. -2 The total amount of metal salt solution B and reducing agent solution D loaded per unit area on the surface of the porous nickel electrode substrate is 0.1-4 mL cm -2 The total volume of the metal salt solution B is 1:1, and the volume ratio of the metal salt solution B and the reducing agent solution D is 1:

1.

9. The thin layer preparation process of a NiMC self-grown hydrogen evolution cathode according to claim 1, characterized in that: The step In step 4, heat treatment is performed in a tubular furnace under nitrogen, air or mixed hydrogen atmosphere at a temperature of 200°C to 500°C. The time is 1 to 3 hours.

Citation Information

Patent Citations

  • Efficient amorphous Ni or NiM hydrogen evolution electrode and preparation method thereof

    CN117926306A

  • Ni / NiMo-coated MoOX self-supporting electrode and preparation method and application thereof

    CN118756204A

  • Preparation method of efficient hydrogen evolution catalyst Mo / Mo2C

    CN118957655A